An overview of the History of Mathematics in degree course projects in mathematics at public higher education institutions in the state of Maranhão - Silva Neto, Benjamim Cardoso da (2024)
The present work aims to present an overview of how the History of Mathematics is present in Mathematics Degree PPCs at HEIs and is based on documentary research around a descriptive analysis about the presence of the History of Mathematics in the pedagogical projects of Courses. This research began with an identification of public Higher Education Institutions in the state in e-MEC, from which we report four institutions, UFMA, IFMA, UEMA and UEMASUL. With the institutions identified, the Pedagogical Projects of the Courses were searched on the websites of each HEI, where readings and studies were undertaken to create a presentation and discussion about the presence of the History of Mathematics in each institution and characterize it. The results are displayed in tables and discussed from which it is inferred that UFMA and UEMASUL have only one Campus that offers the Degree in Mathematics course with a workload of 60 hours, UEMA has five Campuses with this subject with the same workload hourly, and IFMA has seven campuses with this discipline ranging from 45 to 60 hours.